The Influence of Job Environment Factors on Employee Participation in the Organizational Culture of Lao Telecommunication Public Company - Panghasith , Somphavanh; Yangsanesay, Jahue; Indavong, Dalounny (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objectives of this research were to study employee participation in the organizational culture of Lao Telecommunication Public Company, to study the employees' opinions on the job environment factors and to study the influence of job environmental factors on employee participation within the organizational culture of Lao Telecommunication Public Company. The target population for this study was defined as personnel working at the Lao Telecommunication Public Company in the north part of Laos in 2025. The sample consisted of 215 personnel; The research instrument was a questionnaire using a 5-level Likert rating scale. The Cronbach's alpha reliability coefficient for the instrument was excellent at 0.986, The statistics used for data analysis were frequency, percentage, mean, standard deviation, Pearson's product-moment coefficient, and multiple regression analysis. The results found that the employees of Lao Telecommunication public company were participated in the implementation of organizational culture at the most level, including: the most participated part of the employees was the compliance and respect, customer focus culture, For the Integrity, Learning and creativity culture were more participated. The job environment factors were of the most importance to the performance of employees of Lao Telecommunication Public Company, which includes: safety/security and individual characteristics factors, job and structural and management, the job advancement opportunities, Intrinsic aspects, communication and the social aspects. For the wages and welfare or benefits and working conditions, employees were given priority as factors that were more important to their performance. The job environment factors influencing the study employee participation in the organizational culture of Lao Telecommunication Public Company was include 5 factors: safety and security, the intrinsic aspects of the job, Communication, the social aspects of the jobs, and the personal characteristics factors at Statistically significant level of 0.05.